2015
DOI: 10.3390/rs70201937
|View full text |Cite
|
Sign up to set email alerts
|

Regional Equivalent Water Thickness Modeling from Remote Sensing across a Tree Cover/LAI Gradient in Mediterranean Forests of Northern Tunisia

Abstract: Abstract:The performance of vegetation indexes derived from moderate resolution imaging spectroradiometer (MODIS) sensors is explored for drought monitoring in the forests of Northern Tunisia; representing a transition zone between the Mediterranean Sea and the Sahara Desert. We investigated the suitability of biomass and moisture vegetation indexes for vegetation water content expressed by the equivalent water thickness (EWT) in a Mediterranean forest ecosystem with contrasted water budgets and desiccation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…NDVI is an indicator of the vegetation dryness [48] and could be used to assess dry woody vegetation matter, which is the main fuel source in Mediterranean forest wildfires. A decline in NDVIW would imply drying trends in woody vegetation and increasing dry matter for potential fires [47].…”
Section: Pre and Post Fire Assessment Using Ndviw And Ndvih In Mt Camentioning
confidence: 99%
“…NDVI is an indicator of the vegetation dryness [48] and could be used to assess dry woody vegetation matter, which is the main fuel source in Mediterranean forest wildfires. A decline in NDVIW would imply drying trends in woody vegetation and increasing dry matter for potential fires [47].…”
Section: Pre and Post Fire Assessment Using Ndviw And Ndvih In Mt Camentioning
confidence: 99%
“…In a previous research in the Kroumirie forest comparing field moisture data with MVI computed from MODIS [26], it has been shown that MVI are highly correlated to vegetation water content in this ecosystem. In other water limited ecosystems, a study led in Australia confirmed that MVI are sensitive to drought intensity and are highly correlated to SPI [27].…”
Section: Modis Time-series Datamentioning
confidence: 99%
“…Indeed in [26], it has been shown that in this peculiar ecosystem characterized by a gradient of vegetation density, the models linking water-sensitive indexes and the hydric status of the canopy are highly dependent of the biomass expressed by the LAI (Leaf Area Index). This could explain the variable performance of MVI from one site to another as they had different sensitivities to the biomass as reported in other works [27].…”
Section: Drought Analysis By Spi and Modis Time Seriesmentioning
confidence: 99%
“…Helman et al [56] and Chekroun et al [57] used a distinctly different approach to distinguish the contributions of herbaceous and woody vegetation to the VI time signals in their Mediterranean study areas. In contrast to conventional signal decomposition, their approaches were designed a priori to take strategic advantage of two intra-annual periods, the dry season and the wet season, when the seasonal phenology of herbaceous and woody vegetation diverge.…”
Section: Multispectral Image-based Approaches To Mapping Of Semiarid mentioning
confidence: 99%
“…These studies demonstrated that the signal component associated with seasonal herbaceous vegetation could be isolated from the woody signal by exploiting this seasonal divergence in the VI response. Chekroun et al [57] used this approach with several VI data types from the Moderate Resolution Imaging Spectroradiometer (MODIS) to achieve improved sensitivity to drought across landscapes of Northern Tunisia with large variations in the proportional surface cover of trees, shrubs and grass. Helman et al [56] showed this approach is effective for estimating and mapping spatial variation in the subpixel fractional surface cover of woody vegetation and herbaceous vegetation in their study area in Israel.…”
Section: Multispectral Image-based Approaches To Mapping Of Semiarid mentioning
confidence: 99%